Understanding responses to a UK high-voltage powerline proposal: the role of place and project-based social representations - Bailey, E. (2017)
In going beyond the NIMBY (Not In My Backyard) concept, Devine-Wright (2009) posited a place-based approach highlighting the role of social representations of place for understanding responses to energy infrastructure projects. Existing studies (Devine- Wright & Howes, 2010; Anderson, 2013) have investigated the ways in which representations of diverse forms of place change are anchored and objectified symbolically based on existing social representations of place. These studies have shown that the degree of fit between representations of place and proposed place change can be seen to inform community responses to different developments. There is however, a dearth of research investigating the symbolic fit of power line projects amongst existing representations of the English countryside, despite the fact that such projects are both highly controversial and key to ensuring delivery of low-carbon energy policy targets. This paper thus sought to explore social representations of a proposed power line development in Southwest England and their symbolic fit with representations of nearby countryside areas, given the increased deployment of lowcarbon energy infrastructure in this locale. Five focus groups were conducted with residents of a town in North Somerset, to highlight residents' co-constructed place and project-based social representations. Findings from thematic data analysis suggest that those representing the nearby countryside as replete with existing grid infrastructure objectified the power line proposal as an acceptable and 'familiar' form of place change. Conversely, those representing the countryside as 'natural' tended to objectify the proposal as industrialising this locale, objecting to it on this basis. This study reveals the utility of adopting Social Representations Theory to understand responses to proposed energy infrastructure developments given the UK low carbon transition, and suggests that grid companies could enhance acceptance by seeking to minimise the 'industrial' nature of such projects.